FSKTM landscape committee homepage / Gan Wei Leong - Gan , Wei Leong (2002)
FSKTM Landscape Committee Homepage is a web-based application. It aims at providing web application to assist the operation and management of FSKTM Landscape Committee. lt also acts as a communication channel between the faculty students and the landscape committee members. This project is aims to overcome that no such web site for FSKTM Landscape Committee to provide up-to-date information. FSKTM Landscape Committee Homepage is a stand-alone system. It wi ll be developed on the Microsoft Windows 2000 platform. Internet Information Server will be used as web server while Macromcdia Dreamweaver Ultradev 4.0 will be used as a tool for designing dynamic web application for this project. This project is handle by one undergraduate student only. An introductory description about this thesis project consists of project definition, objectives and scope has been discussed in this report. Beside that, some survey and literatures related to this thesis project has been analyzed and carried out. Justification on the methodology using for this project and the requirement analysis is of this project has been discussed briefly in this report too. In addition, this report also discussed briefly about the system design, system implementation, system testing and system evaluation. User manual also attach at then back of this report.